Prevalence of topical corticosteroid use without prescription in Saudi Arabia: A cross-sectional study - Shaikah Al-Aojan; Alanoud Al-Marzoug; Abdulrahman Alaujan; Samiah Abanmi; Mohammed I AlJasser (Wolters Kluwer Medknow Publications, 2021)
Background: Misuse of topical corticosteroids (TCS) is common and constitutes a serious problem in many parts of the world where they can be obtained without prescription. Limited studies have been performed in Saudi Arabia to address this issue. Purpose: We aim to study the prevalence, predisposing factors, and adverse consequences of TCS use without prescription in Saudi Arabia. Methods: A cross-sectional study was performed using an Arabic questionnaire distributed through social media applications in May 2020 in Saudi Arabia. Individuals aged 18 years and above who used TCS within the last 2 years were included. The questionnaire consisted of detailed questions about TCS use and demographic information. Results: A total of 720 participants completed the questionnaire. TCS were used without prescription by 43.1% of respondents. Being female was the only identified risk factor for the use of TCS without prescription. The main reason for purchasing TCS without prescription was that the problem seemed too trivial to consult a physician (36.6%). The most common conditions for which TCS were used were treatment of pruritus without skin disease (23.7%) and cosmetic reasons (19.9%). Side effects were reported in 25.6% of participants. The most common side effects were hypopigmentation, itching, redness, and skin sensitivity. Conclusion: The use of TCS without prescription is prevalent in Saudi Arabia. We recommend that local health authorities regulate the use of TCS.